2010
DOI: 10.1126/science.1184167
|View full text |Cite
|
Sign up to set email alerts
|

Frictional Characteristics of Atomically Thin Sheets

Abstract: Using friction force microscopy, we compared the nanoscale frictional characteristics of atomically thin sheets of graphene, molybdenum disulfide (MoS2), niobium diselenide, and hexagonal boron nitride exfoliated onto a weakly adherent substrate (silicon oxide) to those of their bulk counterparts. Measurements down to single atomic sheets revealed that friction monotonically increased as the number of layers decreased for all four materials. Suspended graphene membranes showed the same trend, but binding the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

109
1,397
7
15

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,634 publications
(1,528 citation statements)
references
References 29 publications
109
1,397
7
15
Order By: Relevance
“…We conclude that neither a nominal error in tip radius measurement nor assumptions related to the indenter-shape can be possibly resolve the anomaly in inferred failure strain. Graphene-tip vdW interaction -Under most circumstances, the interaction between nano-scale contact systems is predominantly the van der Waals (vdW) interaction, arising from instantaneous charge fluctuations [16,17,15]. We have heretofore ignored adhesive interfacial forces in the simulations, and, following Lee, et al and Wei and Kysar, have assumed a frictionless, non-adhesive hard contact between graphene and the indenter.…”
Section: ) Amentioning
confidence: 99%
“…We conclude that neither a nominal error in tip radius measurement nor assumptions related to the indenter-shape can be possibly resolve the anomaly in inferred failure strain. Graphene-tip vdW interaction -Under most circumstances, the interaction between nano-scale contact systems is predominantly the van der Waals (vdW) interaction, arising from instantaneous charge fluctuations [16,17,15]. We have heretofore ignored adhesive interfacial forces in the simulations, and, following Lee, et al and Wei and Kysar, have assumed a frictionless, non-adhesive hard contact between graphene and the indenter.…”
Section: ) Amentioning
confidence: 99%
“…The characters of h-BN make it possible to realize ballistic electronics at room temperature 10,11 . Normally, uniform crystalline h-BN flakes are mostly obtained by mechanical exfoliation from h-BN single crystals 7,[11][12][13][14][15] . However, the flakes are obtained through a highly skilled manual process-mechanical exfoliation and transferring, which is not a scalable method for practical applications.…”
mentioning
confidence: 99%
“…So far, many efforts have been taken on various substrates such as Ni [16][17][18][19][20][21] , Cu 3,[21][22][23][24][25][26][27] , Pt 28,29 , Ru 30,31 and Co 32 to obtain large h-BN crystals via the chemical vapour deposition (CVD) process. However, those grains in h-BN films are very small (usually o50 mm 2 ) because of high nucleation density at the early growth stages 10,11,[15][16][17]19,22 . The small grains lead to high density of grain boundaries and dangling bonds, which are known as structural defects in h-BN 33,34 .…”
mentioning
confidence: 99%
“…Its nanofriction behavior has been investigated mainly by frictional force microscopy [3][4][5]. Measurements on few-layer graphene and single-layer graphene, prepared by micromechanical cleaving on weakly adherent substrates, have revealed that friction monotonically increases as the number of layers decreases [2,6,7], while, surprisingly, recent studies showed that this tendency is inverted when graphene is suspended [8].Here we present the results of a quartz crystal microbalance (QCM) study mainly focused on the sliding of Xe monolayers on graphene (Gr) between 20 and 50 K, a temperature range which has been scarcely investigated in the literature [9], despite its relevance for the formation of condensed two-dimensional phases of many simple gases [10]. In our approach, the gold electrodes of a QCM were covered with Gr because the ample availability of phase diagrams of noble gases monolayers adsorbed on graphite [10] facilitates the interpretation of the QCM sliding measurements [11,12].…”
mentioning
confidence: 99%
“…Its nanofriction behavior has been investigated mainly by frictional force microscopy [3][4][5]. Measurements on few-layer graphene and single-layer graphene, prepared by micromechanical cleaving on weakly adherent substrates, have revealed that friction monotonically increases as the number of layers decreases [2,6,7], while, surprisingly, recent studies showed that this tendency is inverted when graphene is suspended [8].…”
mentioning
confidence: 99%